Modelamento matemático do escoamento turbulento, da transferência de calor e da solidificação no distribuidor e na máquina de lingotamento contínuo - Rodrigo Ottoni da Silva Pereira (2004)
In the present work a group of mathematical models for the continuous casting processn and their principal phenomena was developed. The models comprise the tundish and the strand of the continuous casting machine. The model takes into account: heat transfer, fluid flow (with different K-e type low Reynolds number turbulence models) and masstransfer. The models allow the calculation of: temperature, velocity and turbulence variables profiles, in the two equipments; the carbon concentration profiles in the solidified metal (macrosegregation); the solidified shell thickness in the continuous casting machine;and the length and position of the intermixed steel zone in a grade transition. The tundish models were validated using water model data. The results led to the selection of the turbulence model of Launder and Sharma for use in mathematical models of tundishes. The models showed that the use of flow modifying devices (weir, dam and turbulence supressor) can enhance the tundish performance. These models alsoshowed that experiments with water in scale 1:1 or in scale 1:3 using the similarity criteria of Reynolds or Froude lead to similar results. Mathematical simulations showed that the variation of steel density with temperature should be taken into account in tundish simulations. Mathematical simulation for Acesita tundishes indicate: a greatersteel flowrate leads to a smaller inclusion removal; a lower metal depth in the tundish leads to a lower steel volume discarded in a grade transition; a smaller penetration of submerged nozzle leads to a greater steel volume discarded in a grade transition. The new features of the model of the strand of the continuous casting machine are theinclusion of the effects of nozzle port configuration on the fluid flow and the possibility to make the calculations for the whole strand until it reaches the cutter. The model was validated with temperature measurements in the surface of the strand in the end of thecooling zone. It was shown that the mathematical model should take into account the fluid flow. The model also showed that the strand become completely solid at approximately 13m below the meniscus. The fluid flow affects the process in the first 4 to 5 m of the strand, being important only in the first 2 m. Different nozzle port angles were simulated and it was shown that a port with a downward angle leads to a thicker solidified steel shell in the mould zone. The introduction of the effect of segregation in the model indicates that there is a greater mixing of the steel melt, leading to a greater volume discarded in a grade transition. Finally, user-friendly interfaces were developed, so it would be easier to use the models and make them useful tools for problem diagnosis and process development.